Henry Cole, Edith Nicolls Clarke, ‘The National’, and Thomas Love Peacock - Henisch, Bridget Ann (Petits Propos Culinaires, 2015)
Provides a history of the National Training School for Cookery established in 1874 the first of several such institutions that arose in that era which among other objectives intended to provide a route to a profession for the poor but which also catered to the leisured classes whose daughters and wives, although not needing employment, had need for education and purpose. The novelist Thomas Love Peacock is a link being the grandfather of Edith Nicols Clarke, who took over the School from the founder Henry Cole.